2007
DOI: 10.1577/h06-050.1
|View full text |Cite
|
Sign up to set email alerts
|

Parasite Survey of the Eastern OysterCrassostrea virginicain Coastal Lagoons of the Southern Gulf of Mexico

Abstract: A parasitological study of the eastern oyster Crassostrea virginica from 11 coastal lagoons in the southern Gulf of Mexico in dry and rainy seasons between late 1999 and early 2001 revealed the presence of 36 bacterial, 2 protozoan (Nematopsis prytherchi and Perkinsus marinus), and 4 helminth species (Urastoma cyprinae, Proctoeces maculatus, a Bucephalus sp., and a Tylocephalum sp.). The prevalence and mean abundances for the protozoa and helminths varied widely between locations but were generally below 50%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 13 publications
1
27
0
2
Order By: Relevance
“…This work presents histopathological information on parasites that have not been previously documented in the pleasure oyster; the exception is Perkinsus marinus, for which the occurrence in pleasure oysters was reported by Cáceres-Martínez et al (2008). Hypertrophic gametes, ovocytes, spermatocytes, and germinal cells have been observed in several species of Crassostrea (Farley 1978;Winstead et al 2004;García et al 2006;Aguirre-Macedo et al 2007). This hypertrophy has been linked to infection by a Papillomavirus-like virus (also referred to as belonging to the families Papillomaviridae and Polyomaviridae; García et al 2006;Cheslett et al 2009;Bower and McGladdery 2009).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This work presents histopathological information on parasites that have not been previously documented in the pleasure oyster; the exception is Perkinsus marinus, for which the occurrence in pleasure oysters was reported by Cáceres-Martínez et al (2008). Hypertrophic gametes, ovocytes, spermatocytes, and germinal cells have been observed in several species of Crassostrea (Farley 1978;Winstead et al 2004;García et al 2006;Aguirre-Macedo et al 2007). This hypertrophy has been linked to infection by a Papillomavirus-like virus (also referred to as belonging to the families Papillomaviridae and Polyomaviridae; García et al 2006;Cheslett et al 2009;Bower and McGladdery 2009).…”
Section: Discussionmentioning
confidence: 95%
“…Rickettsiales-like prokaryotes have been found in several species of oysters; they are generally present inside the epithelial cells of primary and secondary digestive diverticula and have been associated with disruption of the epithelial cells but not with mortality episodes (Lauckner 1983;Bower et al 1994;Aguirre-Macedo et al 2007). However, the recurrent presence of RLPs in various oyster species, evidence of tissue alterations like those observed in the present study, and the high prevalence of RLPs indicate the need for detailed taxonomic and physiological studies of these prokaryotes and their effects on the hosts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Martinez et al (2010) have also reported Nematopsis infections occurring in the pleasure oyster, with compression of adjacent cells and disruption of the connective tissue in heavy infections but with little immune response or pathology. It has also been reported that defense mechanisms of oyster can gradually eliminate Nematopsis form its tissues (Bower et al, 1994;Aguirre-Macedo et al, 2007). Azevedo and Cachola (1992) observed very high prevalence (82%) of Nematopsis in cockle causing complete destruction of infected gill cells, while the clam, Ruditapes decussatus collected from same region and period showed very low prevalence (8%).…”
Section: Resultsmentioning
confidence: 91%
“…N. ostrearum and N. prytherchi were reported from oyster growing areas along the Atlantic and Gulf coasts of USA (Winstead et al, 2004;Aguirre-Macedo et al, 2007) while N. mytella was reported from Mytella falcate, Mytella guyanensis and Crassostrea rizophorae from Brazil (Azevedo and Matos 1999;Padovan et al, 2003). Nematopsis spp.…”
Section: Introductionmentioning
confidence: 99%